Revisão sistemática: o conceito e os subtipos de negligência infantil - Vaz , Douglas José Tenório (2015)
The following work sought to systematically review the existing literature on child neglect, identifying what has been produced on this matter on the last ten years, indicating gaps and shortcomings.Moreover, it intended to delimit the understanding of the definition and the types of negligence. In order to achieve that, this systematic review was performed by seeking articles on Journals present on the databases of CAPES, PsycINFO, Scielo and MEDLINE using the listing of the available production on the databases that matched the key words "Neglect" and "Child Neglect", as these are the key concepts for this investigation. This research followed the decade from 2004 to 2014. The key words were inserted on the subject search field resulting in 188 articles. From this point, an inclusion screening was executed on four stages presenting 25 articles as a result on the third stage of the abstracts analysis. Out of those, 7 articles were included on the last inclusion criteria as they discussed the construct of the definition and subtypes of neglect. The conclusion that was reached is that attempting to define and delimit subtypes of neglect is an unfinished path, especially regarding Brazilian academic production. The operational definitions provided by the protection centres are not enough to promote adequate diagnosis and intervention. Thus, it is understood that such data are propellers and motivators for new researches, which, in turn, can develop measurement tools and investigation programmes which are more efficient. These future investigations could aid on the planning of actions characterized by their accuracy and, at the same time, by their caution, taking the complexity present on the negligence phenomenon into consideration.